Age-dependent resistance of a perennial herb, Aristolochia contorta against specialist and generalist leaf-chewing herbivores - Jeong, Se Jong; Nam, Bo Eun; Jeong, Hyeon Jin; Jang, Jae Yeon; Joo, Youngsung; Kim, Jae Geun (Frontiers in Plant Science, 2023)
Plants need to balance investments in growth and defense throughout their life to increase their fitness. To optimize fitness, levels of defense against herbivores in perennial plants may vary according to plant age and season. However, secondary plant metabolites often have a detrimental effect on generalist herbivores, while many specialists have developed resistance to them. Therefore, varying levels of defensive secondary metabolites depending on plant age and season may have different effects on the performance of specialist and generalist herbivores colonizing the same host plants. In this study, we analyzed concentrations of defensive secondary metabolites (aristolochic acids) and the nutritional value (C/N ratios) of 1st-, 2nd- and 3rd-year Aristolochia contorta in July (the middle of growing season) and September (the end of growing season). We further assessed their effects on the performances of the specialist herbivore Sericinus montela (Lepidoptera: Papilionidae) and the generalist herbivore Spodoptera exigua (Lepidoptera: Noctuidae). Leaves of 1st-year A. contorta contained significantly higher concentrations of aristolochic acids than those of older plants, with concentrations tending to decrease over the first-year season. Therefore, when first year leaves were fed in July, all larvae of S. exigua died and S. montela showed the lowest growth rate compared to older leaves fed in July. However, the nutritional quality of A. contorta leaves was lower in September than July irrespective of plant age, which was reflected in lower larval performance of both herbivores in September. These results suggest that A. contorta invests in the chemical defenses of leaves especially at a young age, while the low nutritional value of leaves seems to limit the performance of leaf-chewing herbivores at the end of the season, regardless of plant age.